Supersymmetric $$AdS_6$$ A d S 6 black holes from ISO(3) $$× $$ × U(1) F(4) gauged supergravity - Parinya Karndumri (European Physical Journal C: Particles and Fields)
Abstract We study supersymmetric $$AdS_6$$ A d S 6 black holes from matter-coupled F(4) gauged supergravity coupled to four vector multiplets with $$ISO(3)× U(1)$$ I S O ( 3 ) × U ( 1 ) gauge group. This gauged supergravity admits a maximally supersymmetric $$AdS_6$$ A d S 6 vacuum with $$SO(3)\subset ISO(3)$$ S O ( 3 ) ⊂ I S O ( 3 ) symmetry. We find a number of new supersymmetric $$AdS_2× \mathcal {M}_4$$ A d S 2 × M 4 solutions by performing topological twists along $$\mathcal {M}_4$$ M 4 . For $$\mathcal {M}_4$$ M 4 being a product of two Riemann surfaces $$Σ × \widetilde{Σ }$$ Σ × Σ ~ , we perform a twist by $$SO(2)× U(1)$$ S O ( 2 ) × U ( 1 ) gauge fields and find $$AdS_2× Σ × \widetilde{Σ }$$ A d S 2 × Σ × Σ ~ solutions for at least one of the Riemann surface being negatively curved. For $$\mathcal {M}_4$$ M 4 being a Kahler four-cycle $$\mathcal {M}_{\text {K}4}$$ M K 4 , a twist by $$SO(2)× U(1)$$ S O ( 2 ) × U ( 1 ) gauge fields leads to $$AdS_2× \mathcal {M}_{\text {K}4}^-$$ A d S 2 × M K 4 - solutions for negatively curved $$\mathcal {M}_{\text {K}4}$$ M K 4 . Finally, performing a twist by turning on SO(3) gauge fields in the case of $$\mathcal {M}_4$$ M 4 being a Cayley four-cycle $$\mathcal {M}_{\text {C}4}$$ M C 4 also leads to $$AdS_2× \mathcal {M}_{\text {C}4}^-$$ A d S 2 × M C 4 - solutions for negatively curved $$\mathcal {M}_{\text {C}4}$$ M C 4 . We give numerical black hole solutions interpolating between all of these $$AdS_2× \mathcal {M}_4$$ A d S 2 × M 4 near horizon geometries and the asymptotically locally $$AdS_6$$ A d S 6 vacuum. It is also possible to uplift all of these solutions to type IIB theory via consistent truncations on $$S^2× Σ $$ S 2 × Σ leading to a new class of supersymmetric $$AdS_2× \mathcal {M}_4× S^2× Σ $$ A d S 2 × M 4 × S 2 × Σ solutions.